Validasi Media Pembelajaran dengan Aplikasi Games Wordwall pada Materi Membiasakan Pola Hidup Sederhana dan Menyantuni Dhuafa Kelas XII - Kinasih, Anya Dani; Elsa, Elsa (Lembaga Yasin AlSys, 2024)
This article discusses the important role of learning media development through Wordwall game applications that aim to facilitate the learning process for students and teachers and make learning more interactive. In addition, this article also evaluates the feasibility of Wordwall-based learning media that will be used for material on simple lifestyles and supporting the poor. The research method used is Research and Development (R&D) with the 4D model (define, design, develop, and disseminate). However, this research only reached the develop stage and did not continue to the disseminate stage, because at develop only, the objectives of this research had been achieved. The method used in this research is validation conducted by media experts and material experts, which shows that this media can be applied properly. The validation results from material experts were 91% and 97%, while validation from media experts showed a percentage of 68% and 81%, which means that the developed product is feasible to be applied in the learning process. The use of interactive media such as Wordwall games is very important to improve student understanding and make learning more interesting. Suggestions for improvement from media experts related to aspects that can increase student attractiveness, such as the use of consistent colors and clear instructions or covers. It is hoped that this learning media can create learning that is more interactive, effective, and interesting and in accordance with student needs.